Occupational stress and adaptation of immigrant nurses from the Philippines. (September 2014) - Connor, Jorgia Briones; Miller, Arlene Michaels
Immigrant nurses face multiple challenges that create vulnerability to stress. The purpose of this study was to explore the stresses and work experiences of Filipino immigrant nurses. Specific aims were to identify the perceived sources of work-related and non-work-related stress and describe the factors that influence stress. A cross-sectional qualitative research design was used to gain a holistic understanding of the participants' experiences. Twenty women, 28–48 years old, working as registered nurses in the Chicago metropolitan area were interviewed. The findings showed that participants faced resettlement demands because of unexpected social and living environments. They also experienced communication problems, discrimination and alienation, which interacted with and intensified work-related stressors. In addition, challenges arose from encountering cultural differences. Overall, this study illustrated that stress is dynamic, multidimensional and highly influenced by culture. These findings increase awareness of the types of stressors encountered by immigrant health care providers and urge health care administrators to develop and implement programmes to improve their quality of life. Recommendations for future studies include focusing on the outcomes of cumulative stress among immigrant health care providers.